The two-component system ActJK is involved in acid stress tolerance and symbiosis in Sinorhizobium meliloti - Albicoro, Francisco Javier (2021)
The nitrogen-fixing α-proteobacterium Sinorhizobium meliloti genome codifies at least 50 response regulator (RR) proteins mediating different and, in many cases, unknown processes. RR-mutant library screening allowed us to identify genes potentially implicated in survival to acid conditions. actJ mutation resulted in a strain with reduced growth rate under mildly acidic conditions as well as a lower capacity to tolerate a sudden shift to lethal acidic conditions compared with the parental strain. Mutation of the downstream gene actK, which encodes for a histidine kinase, showed a similar phenotype in acidic environments suggesting a functional two-component system. Interestingly, even though nodulation kinetics, quantity, and macroscopic morphology of Medicago sativa nodules were not affected in actJ and actK mutants, ActK was required to express the wild-type nitrogen fixation phenotype and ActJK was necessary for full bacteroid development and nodule occupancy. The actJK regulatory system presented here provides insights into an evolutionary process in rhizobium adaptation to acidic environments and suggests that actJK-controlled functions are crucial for optimal symbiosis development.